2021
DOI: 10.1007/jhep10(2021)235
|View full text |Cite
|
Sign up to set email alerts
|

Probing new physics in class-I B-meson decays into heavy-light final states

Abstract: With updated experimental data and improved theoretical calculations, several significant deviations are being observed between the Standard Model predictions and the experimental measurements of the branching ratios of $$ {\overline{B}}_{(s)}^0\to {D}_{(s)}^{\left(\ast \right)+}{L}^{-} $$ B ¯ s 0 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 95 publications
1
30
0
Order By: Relevance
“…(s) → D + (s) π − [5][6][7]. Such decays are dominated by colour-allowed tree topologies described by the topological tree-amplitude a 1 (D + L − ).…”
Section: Introductionmentioning
confidence: 99%
“…(s) → D + (s) π − [5][6][7]. Such decays are dominated by colour-allowed tree topologies described by the topological tree-amplitude a 1 (D + L − ).…”
Section: Introductionmentioning
confidence: 99%
“…In this appendix we present some details of the fit results in section 3.3. Figures 6,7,8,and 9 show the one-dimensional and two-dimensional probability distributions of the parameters in the fit (ii), which uses all the available experimental data for B → DP , B → D * P , B → DV with the solution 1 in eq. (2.20), and B → DV with the solution 2 in eq.…”
Section: A Fit Resultsmentioning
confidence: 99%
“…The probability in the low a 1 (m b ) region is suppressed in the fit (ii) as presented by the red-colored distribution. It is found that the preferred regions of a 1 (m b ) differs from the QCDF prediction by more than 2σ in B → DP and D * P , and 1σ in B → DV .The NP interpretations of the deviation in a 1 (m b ) are scrutinized in refs [5,7,9,66]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Final-state interactions may result in an enhancement of B + c → D + ( ) D 0 decay rates [15]. Moreover, contributions from physics beyond the Standard Model could potentially affect fully hadronic B decays [16][17][18].…”
Section: Introductionmentioning
confidence: 99%